Effect of Light Regulation on the Quality of Sweetpotato Sprouts - Zunfu Lv; Simeng Zhang; Guoquan Lu (HortScience, 2021)
Sweetpotato sprouts are buds or young shoots formed under dark or low-light conditions that can be eaten directly by people. This study was conducted to investigate the effects of light intensity and photoperiod on the quality and yield of sweetpotato sprouts and to identify the most suitable production conditions to provide a theoretical basis and technical parameters for the production of these vegetables. Four treatments involving different light intensities and photoperiods were set up: WL-1, WL-2, SL-1, and SL-2. The leaf color, nutritional quality, antioxidant capacity, texture characteristics, and yield of the sweetpotato sprouts were analyzed using Duncan’s new complex range method. The results demonstrated the following: 1) an increase in photoperiod improved leaf brightness and enhanced the appearance of the product, whereas light intensity had little effect on these parameters; and 2) low light intensity increased the yield of sweetpotato sprouts, whereas high light intensity reduced their yield. Under weak light conditions, the quality and yield of sweetpotato sprouts were improved, and their taste was unaffected. Therefore, the condition of 750 μmol·m−2·s−1 for 2 hours/day was chosen to produce crispy, high-quality, and high-yielding sweetpotato sprouts.